Direct Evidence of Plasticity within Human Primary Motor and Somatosensory Cortices of Patients with Glioblastoma. (22nd September 2020) - Gibb, William R.; Kong, Nathan W.; Tate, Matthew C.
Abstract : Glioblastoma multiforme (GBM) is a devastating disease without cure. It is also the most common primary brain tumor in adults. Although aggressive surgical resection is standard of care, these operations are limited by tumor infiltration of critical cortical and subcortical regions. A better understanding of how the brain can recover and reorganize function in response to GBM would provide valuable clinical data. This ability, termed neuroplasticity, is not well understood in the adult human brain. A better understanding of neuroplasticity in GBM could allow for improved extent of resection, even in areas classically thought to have critical, static function. The best evidence to date has demonstrated neuroplasticity only in slower growing tumors or through indirect measures such as functional MRI or transcranial magnetic stimulation. In this novel study, we utilize a unique experimental paradigm to show direct evidence of plasticity via serial direct electrocortical stimulation (DES) within primary motor (M1) and somatosensory (S1) cortices in GBM patients. Six patients with glioblastoma multiforme in or near the primary motor or somatosensory cortex were included in this retrospective observational study. These patients had two awake craniotomies with DES to map cortical motor and sensory sites in M1 and S1. Five of six patients exhibited at least one site of neuroplasticity within M1 or S1. Out of the 51 total sites stimulated, 32 (62.7%) demonstrated plasticity. Of these sites, 14 (43.7%) were in M1 and 18 (56.3%) were in S1. These data suggest that even in patients with GBM in or near primary brain regions, significant functional reorganization is possible. This is a new finding which may lead to a better understanding of the fundamental factors promoting or inhibiting plasticity. Further exploration may aid in treatment of patients with brain tumors and other neurologic disorders.